1996
DOI: 10.1073/pnas.93.18.9948
|View full text |Cite
|
Sign up to set email alerts
|

Isolated rat hepatocytes can signal to other hepatocytes and bile duct cells by release of nucleotides.

Abstract: Intercellular communication among certain cell types can occur via ATP secretion, which leads to stimulation of nucleotide receptors on target cells. In epithelial cells, however, intercellular communication is thought to occur instead via gap junctions. Here [Arg8]vasopressin, phenylephrine, and propidium iodide were from Sigma; fluo-3/AM was from Molecular Probes; suramin was from Biomol (Plymouth Meeting, PA); and indodicarbocyanine (Cy5) was from Biological Detection Systems (Pittsburgh). All other chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 43 publications
5
175
1
Order By: Relevance
“…It has been recently demonstrated that isolated rat hepatocytes can signal to other hepatocytes by the release of ATP, suggesting a novel paracrine signaling pathway exists (51). This finding favors a physiological role of exogenous ATP, which may trigger a protective effect.…”
Section: Table II Effect Of Exogenous Mg-atp On Cytosolic and Mitochomentioning
confidence: 62%
“…It has been recently demonstrated that isolated rat hepatocytes can signal to other hepatocytes by the release of ATP, suggesting a novel paracrine signaling pathway exists (51). This finding favors a physiological role of exogenous ATP, which may trigger a protective effect.…”
Section: Table II Effect Of Exogenous Mg-atp On Cytosolic and Mitochomentioning
confidence: 62%
“…Because forskolin-mediated secretion involves CFTR (Figure 1b) (3)(4)(5), and activation of CFTR in other systems may result in ATP release (19)(20)(21), we investigated whether forskolin-mediated secretion involves autocrine signaling via luminal ATP. IBDU lumens were perfused with either apyrase to hydrolyze luminal ATP or suramin to block apical P2Y receptors (22). Apyrase reduced the forskolin-induced increase in luminal pH by 86%, and suramin reduced the forskolin-induced increase by 90% (n=6, p<0.01; Figure 8a-b).…”
Section: Luminal Atp Is Necessary For Cyclic Amp-mediated Bicarbonatementioning
confidence: 99%
“…Mechanic stimulation of mouse fibroblasts, hepatocytes, or glial cells evokes an increase in Ca 2+ not only in stimulated cells but also in distant cells [100][101][102]. This remote signaling is mediated by ATP or other nucleotides.…”
Section: Atp In Intercellular Communication: Role Of Mast Cellsmentioning
confidence: 99%